Investigating Microstructure and Wear Characteristics of Alloy Steels Used as Wear Plates in Ballast Cleaning Operation in Railways - Pandey M.; Kumar N. (My University, 2025)
Ballast cleaning machines play a pivotal role in maintaining the stability and safety of railway tracks by transferring and redistributing ballast on the tracks. However, the wear plates used in these machines are subjected to extreme conditions, making the assessment of their wear performance crucial. This study scrutinizes the wear performance of two distinct 31Ni10Cr3Mo6 based alloy steels used as wear plates in the ballast cleaning machines. The study compares the initial microstructure and wear properties of German grade steel (Plasser) wear plate with an indigenous grade steel (RDSO) used as an alternative. The results indicate that the indigenous wear plate consistently exhibits higher weight loss across various loading conditions, whereas the Plasser wear plate demonstrates superior wear resistance, particularly at higher loads. This enhanced performance is attributed to relatively larger amount of high-angle grain boundaries, small grain size, and variations in micro-alloying elements. The compositional analysis indicates low carbon content in both wear plates. The microstructural analysis shows that both samples have a single body-centered cubic crystal structure, with a randomly distributed heterogeneous ferritic and cementite phases in a lath-bainitic microstructure. This comprehensive study provides valuable insights into the wear behavior of these alloy steels, contributing to the optimization of alloying materials and desired microstructure for the wear plates in ballast cleaning machines. © 2024 by ASME.